Detrimental effect of eicosapentaenoic acid supplementation on bone following ovariectomy in rats. - Poulsen, R; Kruger, M (2006)
Although several studies have reported a positive effect of n-3 essential fatty acids (EFAs) on bone density post-ovariectomy, the role of specific EFAs has yet to be fully elucidated. In this study, ovariectomised (OVX) rats were supplemented with 0.1 g (LOW) or 1.0 g (HIGH) of eicosapentaenoic acid (EPA)/kg body weight for 9 weeks. Bone mineral density (BMD), 25-hydroxyvitamin D(3) and plasma fatty acid profile were compared to those of OVX and sham animals fed a non-supplemented diet. BMD decreased significantly in all OVX (P<0.001) but not sham rats. There was no difference in BMD between the LOW group and OVX controls. BMD was significantly lower in the HIGH group compared to OVX and sham controls. 25-hydroxyvitamin D(3) levels were significantly higher in both the LOW and HIGH groups compared to OVX controls (P=0.0006 and 0.02, respectively). In conclusion, high-dose EPA supplementation exacerbated the effects of ovariectomy on BMD.